Features of heterogeneous catalytic transformations of strained carbocyclic compounds of the norbornene series - S. A. Durakov; A. A. Kolobov; V. R. Flid (Тонкие химические технологии, 2022)
Objectives. Catalytic processes involving norbornene (NBN) and norbornadiene (NBD) offer exceptional opportunities for the synthesis of a wide range of hard-to-reach polycyclic hydrocarbons. The problems of selectivity and manufacturability of these reactions are fundamentally important for their practical implementation. The aim of this review is to summarize the latest advances in the field of designing heterogeneous catalysts for the preparation and transformation of promising NBN- and NBD-derivatives with the maintenance of a strained carbocyclic framework in isomerization and dimerization reactions of these compounds.Results. Various strategies for the selection of catalysts and prospects for the development of heterogeneous catalysis for syntheses based on NBN and NBD derivatives were considered. The possibility of selective cyclic dimerization and isomerization of NBN and NBD was shown. The factors that affect the direction of the reactions and make it possible to maintain the strained norbornane structure were discussed.Conclusions. An analysis of the current state of this problem showed that at present, the technological parameters of the conversion of NBD and NBN derivatives with the participation of heterogeneous catalysts are significantly inferior to homogeneous systems. In order to improve the productivity of these processes and design catalyst regeneration, further investigations are required. However, some progress in these areas has already been made. In a number of processes, it is possible not only to maintain the strained carbocyclic framework, but also to establish ways to control regio- and stereo-selectivity. In some cases, the use of heterogeneous catalysts allows the process to be direct into a completely new path, which has no analogues for homogeneous systems.